2002
DOI: 10.1074/jbc.m200292200
|View full text |Cite
|
Sign up to set email alerts
|

Secreted and Transmembrane Mucins Inhibit Gene Transfer with AAV4 More Efficiently than AAV5

Abstract: Adeno-associated virus (AAV) is a promising vector for gene transfer in cystic fibrosis. AAV4 and AAV5 both bind to the apical surface of differentiated human airway epithelia, but only AAV5 infects. Both AAV4 and AAV5 require 2,3-linked sialic acid for binding. However, AAV5 interacts with sialic acid on N-linked carbohydrates, whereas AAV4 interacts with sialic acid on O-linked carbohydrates. Because mucin is decorated with O-linked carbohydrates, we hypothesized that mucin binds AAV4 and inhibits gene trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 41 publications
0
54
0
Order By: Relevance
“…However, non-polarized Caco2 cells provide a good intestinal cell type for AAV2/1, 2/2 and 2/5 transduction. Additionally, AAV2/5 could transduce only Caco2 cells that express 2,3-linked sialic acid epitopes (S. Polyak, unpublished data), a cellular receptor for AAV5 [33], which may be reduced or missing on T84 and HT29 cells. The variability in pseudotype tropism observed among cancer cell lines may be due to their cell surface protein heterogeneity [34] or deficient transduction/ translational machinery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, non-polarized Caco2 cells provide a good intestinal cell type for AAV2/1, 2/2 and 2/5 transduction. Additionally, AAV2/5 could transduce only Caco2 cells that express 2,3-linked sialic acid epitopes (S. Polyak, unpublished data), a cellular receptor for AAV5 [33], which may be reduced or missing on T84 and HT29 cells. The variability in pseudotype tropism observed among cancer cell lines may be due to their cell surface protein heterogeneity [34] or deficient transduction/ translational machinery.…”
Section: Discussionmentioning
confidence: 99%
“…Previous gene transfer research has demonstrated the protective limitations of the luminal surface of the gastrointestinal tract. Extracellular barriers such as tight junctions, cell surface glycocalyces, mucus and enzymes may prevent vector entry [33,[39][40][41]. Additionally AAV capsid characteristics can also determine if apical or basolateral infection is more optimal [34,42].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with a role in host defense, mucosal epithelial cells transfected with MUC1 are less susceptible to viral invasion in vitro (9,10), and Muc1 -/-mice in conventional housing develop bacterial conjunctivitis and chronic infection of the reproductive tract (11,12). The respiratory pathogen Pseudomonas aeruginosa binds MUC1, inducing phosphorylation of the cytoplasmic domain (4), demonstrating that MUC1 signals in response to bacteria.…”
Section: Introductionmentioning
confidence: 92%
“…Patients with COPD, cystic fibrosis and asthma show goblet cell metaplasia and this may be one of the reasons these patients are more susceptible to rhinovirus infection. In addition, airway epithelial mucins also interact with several other respiratory pathogens including Pseudomonas aeruginosa, Staphylococcus aureus, Heamophilus influenza, Streptococcus pneumonia, Burkholderia cenocepacia, influenza virus, adenovirus and coronavirus (Landry et al, 2006;Matrosovich and Klenk, 2003;Plotkowski et al, 1993;Ryan et al, 2001;Walters et al, 2002). The bound pathogens which are cleared under normal conditions, persist in the airway lumen when the mucociliary clearance is impaired and initiate inflammatory response and damage the airway epithelium.…”
Section: Mucociliary Clearancementioning
confidence: 99%